2008
DOI: 10.1007/s11547-008-0350-x
|View full text |Cite
|
Sign up to set email alerts
|

64-detector row CT cystography with virtual cystoscopy in the detection of bladder carcinoma: preliminary experience in selected patients

Abstract: VC and CTC with 64-slice CT are promising diagnostic techniques for bladder cancers measuring 1-5 mm. Further studies on larger patient populations are required to validate our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…This consideration is, however, based on data published by Sadow et al [20], which appear more encouraging than those observed in our series. Recently, the use of CT cystography with virtual cystography has been proposed [21]. In selected patients, this examination showed a high level of diagnostic accuracy, higher than that of conventional CT urography, especially in lesions <5 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This consideration is, however, based on data published by Sadow et al [20], which appear more encouraging than those observed in our series. Recently, the use of CT cystography with virtual cystography has been proposed [21]. In selected patients, this examination showed a high level of diagnostic accuracy, higher than that of conventional CT urography, especially in lesions <5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…ematuria microscopica ma a basso rischio per neoplasia vescicale, sebbene questa considerazione si basi sui dati pubblicati da Sadow et al [20], che risultano più rassicuranti di quelli della nostra casistica. Recentemente è stato proposto anche l'uso di un esame di cistografia TC con cistografia virtuale [21]. Tale esame ha dimostrato un'elevata accuratezza diagnostica in pazienti selezionati, maggiore rispetto all'esame uro-TC convenzionale, particolarmente nelle lesioni sotto i 5 mm, va peraltro rilevato come tale esame sia piuttosto indaginoso e soprattutto come non risponda completamente al quesito clinico di ricerca della causa di ematuria, limitandosi allo studio vescicale, agevolmente, seppur invasivamente effettuato dagli urologi, mentre le alte vie escretrici rimangono escluse dalla valutazione.…”
Section: Discussionunclassified
“…The accuracy of detecting bladder lesions (<1 cm) by computed tomography virtual cystoscopy (CTVC) has been variously reported ranging within 60–100% [ 7 , 10 12 ]. Even bladder lesions <5 mm have also been reportedly detected by some authors utilizing CTVC [ 13 15 ], while others have found the visualization of such lesions to be difficult [ 10 ]. This technology is considered safe for bladder cancer follow-up with detection rates comparable to conventional cystoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…However, disadvantages such as patient discomfort, risk of urinary sepsis, and possible injury of the urethra with subsequent urethral stenosis render this procedure invasive not to mention expensive considering the long follow-up of bladder cancer patients [1, 35]. …”
Section: Introductionmentioning
confidence: 99%